Global Assessment Report on Disaster Risk Reduction 2024 - United Nations Office for Disaster Risk Reduction (United Nations, 2024)
The GAR Special Report 2024 helps to build resilience by asking: How can we learn from recent disasters? How can we protect more people when the next hazard hits? How can we reduce the hazard risks to minimize death and destruction and to avoid disasters? The report applies ‘forensic’ disaster analysis to look at ten recent events, aiming to understand better the unique footprints - or disaster DNA - of these specific occasions. Forensic Investigations of Disasters (FORIN) aims to improve the understanding of disaster risk construction and disasters. It offers policy options and evidence-based recommendations for better corrective, as well as prospective, approaches to integrate disaster risk reduction into development policy and processes. This involves identifying underlying causes, risk drivers, and entry points for decision making so that risks can be recognized, evaluated, and addressed.